MONITORING OF SOME DISASTER AREAS IN INDONESIA USING ARCVIEW 3.3: MONITORING OF SOME DISASTER AREAS IN INDONESIA USING ARCVIEW 3.3 - Ikhsan Parinduri (Institute of Computer Science (IOCS), 2021)
The results of research using Arcview 3.3 disaster mapping to provide information on handling and anticipating handling. Paramater coordinates area map format.shp region, district. Then select the hazard zone in the disaster area. Data reading is inputted by the view and layout menu. The reading of the map image is seen as the color slice of the Resolution Dataseet display. There are data overlay scoring equations for calculation of parameters. Combined maps are given average percentage weighting according to hazard areas. The data at the trackng point is in the form of a digital image in the form of an interpolated earth form on the attribute.